Do Physical Activity and Sleep Correlate with Patient-Reported Outcomes in Total Hip Arthroplasty? - Tang, Alex; Behery, Omar A.; Singh, Vivek; Yeroushalmi, David; Davidovitch, Roy; Schwarzkopf, Ran (The Journal of Hip Surgery, 2021)
Patients have increasingly high expectations of return to activity following total hip arthroplasty (THA). The current literature demonstrates marked improvements in subjective patient-reported satisfaction, and pain and functional outcomes following THA. However, there is limited evidence showing objective improvement in gait and sleep measures. The purpose of this study was to compare accelerometry-measured physical activity and sleep to patient-reported outcomes following THA.A nonrandomized, prospective cohort study was performed at a single institution from 2017 to 2019. Patients were included in the study if they were ≥ 18 years old, had a primary diagnosis of osteoarthritis of the hip, and were undergoing primary, elective THA. Eligible patients received a tracker device upon enrollment which recorded the average number of daily steps and minutes slept at baseline, 1 to 2 weeks, 1 month, and 3 months postoperatively. Hip disability and osteoarthritis outcome score for joint replacement (HOOS Jr) scores were recorded at the same intervals. Paired two-tailed t-tests and chi-squared analyses were performed to compare means. Pearson correlation tests were utilized to determine the correlation between objective measurements and HOOS Jr.Fifty subjects were enrolled, however, only 41 had sufficient data for analysis at 3-month follow-up. Patients demonstrated improved HOOS Jr scores from preoperatively to 2 weeks (p < 0.001) and 3 months (p < 0.001) postoperatively. Average daily steps ambulated and minutes slept preoperatively were statistically similar to average daily steps and minutes slept 3 months postoperatively (p = 0.67 and p = 0.24, respectively). Pearson correlation models only detected a weak negative correlation between average steps preop and preop HOOS Jr (r = –0.401, p = 0.013).Patients returned to similar ambulation distances and sleep time by 3 months postoperatively. Changes in accelerometry-measured activity level and sleep may not correlate with functional outcomes in early follow-ups after THA. While patients report improvements in subjective clinical outcomes, our findings suggest a return to preoperative levels in objective measures at 3 months post-THA.
Keywords: total hip arthroplasty; patient reported outcomes; physical activity; sleep